Antibacterial Compounds of Canadian Honeys Target Bacterial Cell Wall Inducing Phenotype Changes, Growth Inhibition and Cell Lysis That Resemble Action of β-Lactam Antibiotics - Brudzynski, Katrina; Sjaarda, Calvin (PLOS ONE, 2014)
Honeys show a desirable broad spectrum activity against Gram-positive and negative bacteria making antibacterial activity an intrinsic property of honey and a desirable source for new drug development. The cellular targets and underlying mechanism of action of honey antibacterial compounds remain largely unknown. To facilitate the target discovery, we employed a method of phenotypic profiling by directly comparing morphological changes in Escherichia coli induced by honeys to that of ampicillin, the cell wall-active β-lactam of known mechanism of action. Firstly, we demonstrated the purity of tested honeys from potential β-lactam contaminations using quantitative LC-ESI-MS. Exposure of log-phase E. coli to honey or ampicillin resulted in time- and concentration-dependent changes in bacterial cell shape with the appearance of filamentous phenotypes at sub-inhibitory concentrations and spheroplasts at the MBC. Cell wall destruction by both agents, clearly visible on microscopic micrographs, was accompanied by increased permeability of the lipopolysaccharide outer membrane as indicated by fluorescence-activated cell sorting (FACS). More than 90% E. coli exposed to honey or ampicillin became permeable to propidium iodide. Consistently with the FACS results, both honey-treated and ampicillin-treated E. coli cells released lipopolysaccharide endotoxins at comparable levels, which were significantly higher than controls (p<0.0001). E. coli cells transformed with the ampicillin-resistance gene (β–lactamase) remained sensitive to honey, displayed the same level of cytotoxicity, cell shape changes and endotoxin release as ampicillin-sensitive cells. As expected, β–lactamase protected the host cell from antibacterial action of ampicillin. Thus, both honey and ampicillin induced similar structural changes to the cell wall and LPS and that this ability underlies antibacterial activities of both agents. Since the cell wall is critical for cell growth and survival, honey active compounds would be highly applicable for therapeutic purposes while differences in the mode of action between honey and ampicillin may provide clinical advantage in eradicating β-lactam-resistant pathogens.